تقييم أثر أمن المعلومات على أداء المصارف - بوكر الغزيويد. إبتسام إبراهيم (Aljameai, 2024)
المستخلص: تهدف هذه الدراسة إلى تقييم أثر أمن المعلومات على أداء المصارف في قطاع المصرفى لعام 2020/2021, لعينة تتكون من 13 مصرفاً، بينما يبلغ مجتمع البحث 32 فرعاً مصرفياً، وقد تم قياس أمن المعلومات من خلال الإجراءات الخاصة بتطبيق معايير أمن المعلومات ومقاييس نظام حماية الخدمات المصرفية الإلكترونية, وسرعة معالجة تهديدات أمن المعلومات, وذلك فى محاولة لمعرفة تأثير تلك المتغيرات المستقلة على مؤشرات الربحية وجودة الأصول. وتم تحليل أثر أمن المعلومات على الأداء بالمصارف بإستخدام أسلوب تحليل الانحدار المتعدد واختبار کا تربیع (Chi-Square), وأوضحت النتائج جوهرية أثر أمن المعلومات على مؤشرات الربحية التي تمثلت في (معدل العائد على الأصول, ومعدل العائد على الملكية ومعدل العائد على رأس المال), وكذلك على جودة الأصول التي تمثلت فى نسبة مخصصات خسائر القروض. Abstract: This research aims to assess the impact of information security on the performance of banks in the banking sector for the year 2020/2021, for a sample consisting of 13 banks, while the research community is 32 bank branches, and information security has been measured through the procedures for applying information security standards and banking services protection system standards electronic data, and the speed of processing information security threats, in an attempt to find out the impact of these independent variables on indicators of profitability and asset quality. The impact of information security on performance in banks was analyzed using the method of multiple regression analysis and the Chi-Square test. As well as on the quality of assets, which was represented in the ratio of provisions for loan losses.